Role of Echocardiography in Diagnosis and Treatment of Patients with Infective Endocarditis - Srbinovska Кostovska, Elizabeta; Tosev, Slavco; Andova, Valentina; Antova, Emilija (Македонско лекарско друштво = Macedonian Medical Association, 2014)
Abstract Infective endocarditis is an endovascular microbial infection of cardiovascular structures, localized on valves, large intrathoracic vessels, ventricular and atrial endocardium and prosthetic materials. IE may present as an acute, subacute and chronic disease. The incidence of IE ranges from one country to another within 3-10 episodes/100.000 persons per years. The classification of IE according to the localization of the infection is: left-sided native valve IE, left-sided prosthetic valve IE (PVE), right-sided IE and device-related IE. Echocardiography plays a key role in each of the steps of assessment of IE: the diagnosis, risk stratification and follow-up of patients with infective endocarditis. The major echocardiographic criteria for IE are discovering vegetations, abscess, new valvular regurgitation and prosthesis dehiscence. According to the recent ESC recommendation for diagnosis and assessment of patients with IE, in all patients with clinical suspicion of IE, transthoracic echocardiography (TTE) is the first step of assessment. If we speak about patients with prosthetic endocarditis, then transoesophageal echocardiography (TEE) is recommended in case of poor quality of TTE and in majority of patients with positive TTE. If TTE examination is negative with low suspicion of IE, further follow-up has to be stopped. If TTE is negative but there is a high suspicion of IE, TEE has to be repeated in 7-10 days. Anatomical features on IE echocardiography have specific characteristics: vegetation, destructive valve lesion (perforation, prolapse of the valve) and abscess formation (more frequent in Ao valve and in prosthetic valve), which can be complicated with pseudoaneurysm and fistulization). Other cardiac imaging modalities (multislice computed tomogramphy (CT), magnetic resonance, 18F-fluorodesoxyglucose PET-CT, and single photon emission computed tomography (SPECT) /CT sometimes can be used in discovering complications in IE. Conclusion: Echocardiography is useful in diagnosis of endocarditis, assessment of the severity of the disease, prediction of short-term and long-term prognosis, prediction of embolic risk, management of its complications, as well as deciding whether to operate or not and in choosing optimal time for surgery and follow-up.